SME Internationalization Intelligence Information and Knowledge on International Opportunities - Senik, Zizah Che; Md. Sham, Ridzuan (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2011)
Small and medium enterprises (SMEs) internationalization intelligence, referring to the process of gathering information and knowledge on international opportunities, is crucial to initiate SMEsâ internationalization. The literature has stressed organizational resources, networks and information sharing as means to acquire internationalization intelligence, suggesting that the resource-based, network and social capital perspectives can be adopted to explore this issue. However, previous literature still lacks evidence on how SMEs acquire relevant intelligence, and who or what are involved with the process. To address this lack of evidence, we interviewed 54 SME owners/key personnel in the manufacturing sector to: identify sources of internationalization intelligence; examine how those sources assist SMEs to internationalize; and develop propositions on internationalization intelligence. Analyzing the data using NVivo, four themes emerged including institutions, business associates, personal efforts, and other means. The analysis suggests internationalization intelligence occurs mainly through the networks of the SME owners/key personnel, built on their firmâs resources through their internal and external information sharing activities, indicating the need of the SMEs to position themselves in their environments. These findings are developed into propositions. The study indicates multiple perspectives in conceptualizing the process of internationalization intelligence. This study advances a conceptualization of internationalization intelligence, and offers avenues for future research.Â Â Â Â Â Â